A ministry of (not-so-silly) walks: Investigating classifier handshapes for animate referents in DGS - Lettow Isabeau; Loos Cornelia (Open Linguistics)
Across sign languages, classifier predicates depict the movement, location, or manipulation of (in-)animate entities. Each classifier predicate contains a classifier handshape that represents a referent based on one or more of its salient semantic and/or visual properties. In this article, we focus on a subset of entity classifiers in German Sign Language (DGS) that depict the movement and/or position of animate referents: The ‘1’-classifier, the ‘V’- or inverted ‘2’-classifier, and a general entity classifier. The distribution of these classifiers has been claimed to be determined by semantic and pragmatic factors in other sign languages. Looking at 16 re-tellings of the Canary Row cartoons, we perform an exploratory analysis showing that syntactic, semantic, and discourse-pragmatic factors influence the choice of one classifier over another when the basic set of entities depicted – anthropomorphized animates – is held constant.